Dampak Disiplin kerja, Kompensasi, Servant Leadership dan Kepuasan Kerja terhadap Kinerja Dosen di Perguruan Tinggi (International Forum of Researchers and Lecturers, 2023)
The purpose of this study is to discuss how a servant leader is an honest, responsible leader and can delegate tasks to his subordinates. Higher education rectors in implementing servant leadership can also increase the satisfaction and performance of the lecturers they lead. Work discipline can encourage the creation of satisfaction and performance of lecturers in tertiary institutions. This research was conducted with the aim of knowing the impact of work discipline, compensation, servant leadership and job satisfaction on the performance of lecturers at the Indonesian Muslim University. This study used a quantitative approach with a total of 52 respondents as research subjects. Methods of data processing using path analysis (path analysis) and descriptive statistical methods. From the results of the study it was concluded that servant leadership does not have an effect on job satisfaction, compensation has a positive effect on employee performance, the greater the compensation, the greater the employee morale, work discipline has a positive effect on job satisfaction, servant leadership has a positive effect on lecturer performance, discipline work has a positive effect on lecturer performance, and job satisfaction has no effect on lecturer performance..